POTENTIAL DISTRIBUTION OF Musa velutina (MUSACEAE) IN PROTECTED WILD AREAS OF COSTA RICA - Morera-Chacón, Brayan Heiner (2016)
By using the maximum entropy algorithm (MaxEnt) model, this study determined which protected wild areas are suitable habitats for Musa velutina. The variables used were biotemperature, precipitation, humidity, and the altitude level obtained from the 2008 atlas of the Costa Rican Technological Institute (TEC, for its name in Spanish). The model shows good performance according to the area under the curve (AUC = 0.824). Areas with higher levels of suitable habitats were located in moderate elevation levels on the Caribbean slope. When the contribution of variables were analyzed, the largest contributor to the model was biotemperature. M.velutina is widely distributed in many protected areas in Costa Rica, which can be an ideal environment for their establishment and high potential to become invasive. This model of potential species distribution is of great value when generating strategies for a more efficient use of resources and for predicting potential scenarios. This knowledge allows increasing success in conservation projects and management.